2022
DOI: 10.1177/00033197221087777
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Immune-Inflammation Index as a Predictor of Microvascular Dysfunction in Patients With Cardiac Syndrome X

Abstract: The systemic immune inflammation index (SII; platelet count x neutrophil-lymphocyte ratio), a new marker, predicts adverse clinical outcomes in many conditions, including acute and chronic coronary syndromes, pulmonary embolism, cancers, and contrast nephropathy. The aim of this study was to determine the relationship between SII and microvascular dysfunction in patients with Cardiac Syndrome X (CSX); 105 patients with CSX and 105 patients with normal coronary arteries were included. Microvascular dysfunction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Therefore, an elevated SII value indicated more severe immune-mediated and inflammation-mediated brain damage, which plays a critical role in the pathogenesis of POD [5,22]. Moreover, many studies have indicated that the SII is associated with different cancers [25][26][27], ischaemic stroke [18,28], and cerebral small vessel disease [16,29,30]. Individuals suffering from small vessel disease have more fragile brains, in which areas of vascular dysfunction can be more susceptible to acute impairment following systemic inflammatory insults [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an elevated SII value indicated more severe immune-mediated and inflammation-mediated brain damage, which plays a critical role in the pathogenesis of POD [5,22]. Moreover, many studies have indicated that the SII is associated with different cancers [25][26][27], ischaemic stroke [18,28], and cerebral small vessel disease [16,29,30]. Individuals suffering from small vessel disease have more fragile brains, in which areas of vascular dysfunction can be more susceptible to acute impairment following systemic inflammatory insults [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown the potential value of the NLR, PLR, and PWR in predicting POD after lower limb, head and neck free-flap reconstruction, total hip arthroplasty, abdominal surgery, oesophagectomy carotid endarterectomy, and cardiac surgery [11][12][13][14][15]. As a white-cell derived inflammatory biomarker, systemic immune inflammation index (SII) has been used to predict ischemic stroke, delayed vasospasm, microvascular dysfunction, and acute kidney injury [16][17][18][19]. However, the SII has not been applied to predict POD in elderly patients after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…SII is a new inflammatory index that comprehensively reflects the host immune and inflammatory state balance [ 20 ]. A high SII score is associated with adverse outcomes in cancer patients, heart failure, and coronary artery disease [ 7 ]. It has even been proposed that SII is more useful than NLR and PLR alone in predicting inflammatory status and prognosis in a variety of clinical scenarios [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hematological parameters such as WBC, hemoglobin (Hgb), hematocrit (HTC), neutrophil count (NEU),lymphocyte (LYM) , monocyte (MON), platelet (PLT), RDW, NLR, MLR, RLR, and SII values were recorded. SII was calculated by multiplying PLT count and NLR [ 7 ]. In addition, CRP values were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…SII has been used in past studies to predict and evaluate the prognosis of various solid tumors, such as gastric cancer ( 16 , 17 ), non-small cell lung cancer ( 18 , 19 ), pancreatic cancer ( 20 ), and esophageal cancer ( 21 , 22 ). In addition, SII also has a high value for the prognosis of cardiovascular disease ( 23 27 ). Inflammation is a hallmark of NAFLD progression, and the recruitment of circulating inflammatory cells and the upregulation of inflammatory mediators play an important role in hepatic steatosis and fibrosis ( 28 31 ).…”
Section: Introductionmentioning
confidence: 99%